Electroacupuncture at ST36 (Zusanli) Prevents T-Cell Lymphopenia and Improves Survival in Septic Mice - Lv ZY; Shi YL; Bassi GS; Chen YJ; Yin LM; Wang Y; Ulloa L; Yang YQ; Xu YD (Dove Medical Press, 2022)
Zhi-Ying Lv,1,* Yang-Lin Shi,1,* Gabriel Shimizu Bassi,1 Yan-Jiao Chen,1 Lei-Miao Yin,1 Yu Wang,1 Luis Ulloa,2 Yong-Qing Yang,1 Yu-Dong Xu1 1Shanghai Research Institute of Acupuncture and Meridian, Yueyang Hospital of Integrated Traditional Chinese and Western Medicine Affiliated to Shanghai University of Traditional Chinese Medicine, Shanghai, People's Republic of China; 2Department of Anesthesiology, Duke University, Durham, NC, USA*These authors contributed equally to this workCorrespondence: Yu-Dong Xu; Yong-Qing Yang, Email xuyudong@shutcm.edu.cn; yyq@shutcm.edu.cnPurpose: Sepsis is the main cause of death in intensive care unit. Maladaptive cytokine storm and T-cell lymphopenia are critical prognosis predictors of sepsis. Electroacupuncture (EA) is expected to be an effective intervention to prevent sepsis. This study aims to determine the potential of EA at ST36 (Zusanli) to prevent experimental septic mice.Methods: Mice were randomly assigned into PBS, LPS, or EA+LPS group. EA (0.1 mA, continuous wave, 10 Hz) was performed stimulating the ST36 for 30 min, once a day for 3 days. After the third day, all mice were challenged with PBS or LPS (4 mg/kg) simultaneously. Mice were evaluated for survival, ear temperature, and other clinical symptoms. Lung and small intestine tissue injuries were analyzed by hematoxylin and eosin staining. Bio-Plex cytokine assay was used to analyze the concentration of cytokines. T lymphocytes were analyzed by flow cytometry and Western blot assays. The role of T cells in preventing sepsis by EA was analyzed by using nude mice lacking T lymphocytes.Results: EA at ST36 improved survival, symptom scores, and ear temperature of endotoxemic mice. EA also improved dramatically pulmonary and intestinal injury by over 50% as compared to untreated mice. EA blunted the inflammatory cytokine storm by inducing a lasting inhibition of the production of major inflammatory factors (TNF-α, IL-1β, IL-5, IL-6, IL-10, IL-17A, eotaxin, IFN-γ, MIP-1β and KC). Flow cytometry and Western blot analyses showed EA significantly reduced T-lymphocyte apoptosis and pyroptosis. Furthermore, T lymphocytes were critical for the effects of EA at ST36 stimulation blunted serum TNF-α levels in wild-type but not in nude mice.Conclusion: EA halted systemic inflammation and improved survival in endotoxemic mice. These effects are associated with the protective effect of EA on T lymphocytes, and T cells are required in the anti-inflammatory effects of EA in sepsis.Keywords: electroacupuncture, sepsis, inflammation, cytokine storm, lymphopenia